Penerapan Problem Based Learning (PBL) Menggunakan Indeks Card Match (ICM) untuk Meningkatkan Hasil Belajar Matematika Materi Desimal Kelas IV SDN Klampis Ngasem I/246 Surabaya - Andra Ena Fitri Mega Ramadani; Wiryanto Wiryanto; Naila Rosyada (Journal on Education, 2023)
The purpose of this study is to see an increase in the results of cognitive and affective mathematics of learners and the learning process in grade IV C of Klampis Ngasem I/246 Surabaya Elementary School. The increased study efforts are made by applying Problem-Based Learning (PBL) using Index Card Match (ICM). The study is a collaborative class action study between students and class teachers with the students of IV C of Klampis Ngasem I/246 Surabaya Elementary School for 31 students as research subjects. The object of research is the product of learning mathematics through the application of Problem-Based Learning (PBL) using Index Card Match (ICM) in the decimal matter. The study is conducted during two cycles, each cycle being a single meeting by collection techniques are done with tests and observations. Data analysis techniques of research use statistical quantitative analysis and descriptive qualitative analysis. Research shows that there is an increase in mathematical learning after applying Problem-Based Learning (PBL) to cycle 1 and using Index Card Match (ICM) in cycle 2. The cognitive value from 57.87 on the implementation of diagnostic assessment to 61.79 on cycle 1 and increased again to 74.04 in cycle 2 , then the process of learning by applying Problem-Based Learning (PBL) using Index Card Match (ICM) is rated to increase the learning result of students' learning.